Social Segregation in Secondary Schools: How Does England Compare with Other Countries? - Stephen P. Jenkins; John Micklewright; Sylke Viola Schnepf (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
We provide new evidence about the degree of social segregation in England?s secondary schools, employing a cross-national perspective. Analysis is based on data for 27 rich industrialised countries from the 2000 and 2003 rounds of the Programme of International Student Assessment (PISA), using a number of different measures of social background and of segregation, and allowing for sampling variation in the estimates. England is shown to be a middle-ranking country, as is the USA. High segregation countries include Austria, Belgium, Germany and Hungary. Low segregation countries include the four Nordic countries and Scotland. In explaining England?s position, we argue that its segregation is mostly accounted for by unevenness in social background in the state school sector. Focusing on this sector, we show that cross-country differences in segregation are associated with the prevalence of selective choice of pupils by schools. Low-segregation countries such as those in the Nordic area and Scotland have negligible selection in schools. High segregation countries like Austria, Germany and Hungary have separate school tracks for academic and vocational schooling and, in each case, over half of this is accounted for by unevenness in social background between the different tracks rather than by differences within each track.
Keywords: 330